While time remains : a North Korean defector's search for freedom in America - Park, Yeonmi, 1993- (Threshold Editions, 2023)
"The North Korean defector, human rights advocate, and bestselling author of In Order to Live sounds the alarm on the culture wars, identity politics, and authoritarian tendencies tearing America apart. After defecting from North Korea, Yeonmi Park found liberty and freedom in America. But she also found a chilling crackdown on self-expression and thought that reminded her of the brutal regime she risked her life to escape. When she spoke out about the mass political indoctrination she saw around her in the United States, Park faced censorship and even death threats. In While Time Remains, Park sounds the alarm for Americans by highlighting the dangerous hypocrisies, mob tactics, and authoritarian tendencies that speak in the name of wokeness and social justice. No one is spared in her eye-opening account, including the elites who claim to care for the poor and working classes but turn their backs on anyone who dares to think independently. Park arrived in America eight years ago with no preconceptions, no political aims, and no partisan agenda. With urgency and unique insight, the bestselling author and human rights activist reminds us of the fragility of freedom, and what we must do to preserve it"--